Recent developments in copper-catalyzed radical alkylations of electron-rich π-systems - Shimkin, Kirk W.; Watson, Donald A. (Beilstein Journal of Organic Chemistry, 2015)
Recently, a number of papers have emerged demonstrating copper-catalyzed alkylation reactions of electron-rich small molecules. The processes are generally thought to be related to long established atom-transfer radical reactions. However, unlike classical reactions, these new transformations lead to simple alkylation products. This short review will highlight recent advances in alkylations of nitronate anions, alkenes and alkynes, as well as discuss current mechanistic understanding of these novel reactions.
Keywords: alkene; alkylation; alkyne; catalysis; copper; nitroalkane; radical